Persepsi dan Harapan Penumpang Terhadap Pelayanan Maskapai Garuda Indonesia di Bandar Udara Internasional Zainudin Abdul Madjid Lombok - Ella Dian Praharyati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze passenger satisfaction and determine the service quality attributes of Garuda Indonesia Airlines at Zainuddin Abdul Majid International Airport Lombok that need to be developed. This research was conducted for one month, using five main dimensions of service quality, namely the appearance of elements or physical/tangibles, reliability, responsiveness, assurance, and empathy. The sample of this research is Garuda Indonesia airline passengers. The sample in this study used purposive sampling method. Data was collected by means of questionnaires, documentation, and literature study. The research method uses a quantitative research design in the form of a survey with Service Quality (Servqual) and Importance Performance Analysis (IPA) analysis. The results of this study indicate the physical dimensions or tangibles (tangible) passengers are not satisfied with the average value of the gap (-0.055), the reliability (reliability) passengers are satisfied with the average value of the gap (0.08), responsiveness (responsiveness) passengers are satisfied with the average value of the gap (0.285), guarantee (assurance) passengers are satisfied with the average value of the gap (0.105), empathy (emphty) shows passengers are satisfied with the average value (0.03). It can be concluded that Garuda Indonesia passengers at Zainuddin Abdul Madjid International Airport Lombok were satisfied with the services provided with an average value (0.089). Attributes that can be developed in order to improve the quality of service in this study are found in the P18 attribute (aircraft crew should pay individual attention) on the empathy dimension.